(untitled) (Third Sector Social Economic Review, 2019)
Globalization, technological development, increasing competition and the change in the labor market also affected the human resources management’s role in the businesses. Businesses have to revise their personnel needs to keep up them. The main aim of this study is to examine the need of personnel for the a few number of large-sized businesses and small-sized and medium-sized businesses(SME) in Kırıkkale with the effect of globalization. For this purpose, an information form was applied to 150 businesses in Kırıkkale by face to face interviews. In the analysis of the data obtained, t-test and variance analysis were performed. In this context, in order to meet the needs of the personnel in the province, the local dynamics of Kırıkkale University and other vocational high schools, the departments to be opened to vocational education institutions, the compatibility of the characteristics of the students to be graduated to the market, and the solutions to the problems have been proposed.